Identity Theft Awareness in North Central West Virginia - Goodrich, Gwendolyn Lea (2003)
Identity theft occurs when an individual takes over the identity of another without that person's consent or when someone uses bits and pieces of information about an individual to represent himself or herself as that person for fraudulent purposes. The simplicity of gathering personal identification through technology enhancements has made identity theft reportedly the fastest growing crime in the U.S. The latest report indicates, through a national survey, that 20 percent of Americans are victims of identity theft. However, the impact of this growing crime has not been assessed in North Central West Virginia, where this study occurred. The theory is that, even with colleges and a federal law enforcement agency in the area, the majority of residents do not know about identity theft or what to do if they are victimized. Through this study, however, it was determined that the residents of this area are mostly aware of identity theft and what to do if they are victimized